PENYUSUNAN BAHAN AJAR BERBASIS VLOG DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI MAHASISWA PGSD IKIP SILIWANGI - Ronny Mugara; Galih Dani Septiyan Rahayu; Hana Sakura Putu Arga (IKIP Siliwangi Bandung, 2019)
This research is motivated by the importance of increasing the creativity of prospective educators in making innovative instructional media based on online technology as a challenge in the revolutionary era 4.0 and student communication skills that have not been maximized. Therefore, research on the preparation of vlog-based teaching materials is carried out in an effort to improve student communication skills. The method used in this study was quasi-experimental with a non-equivalent pretest posttest control group design. The population in this study were all PGSD students in the 4th of the 2018-2019 academic year with the selected sample namely regular class A1 students as the experimental class and regular A2 class students as the control class. The instrument used in this study is the observation sheet according to communication skills indicators. The results showed an increase in communication skills in PGSD students by making compilation of vlog-based teaching materials.